(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This study examined the effects of iron (Fe) microelementosis on the morphological and microcirculatory structure of the thyroid gland in white rats. The experimental group demonstrated thickening of vascular walls, perivascular fibrosis, alteration of follicular diameters, and increased collagen fiber density. Morphometric analysis revealed a significant reduction in epithelial height, capillary diameter, and follicular area, indicating microcirculatory disturbances and stromal imbalance caused by iron deficiency. These findings emphasize the importance of Fe homeostasis in maintaining the morphofunctional integrity of the thyroid gland.